2017
DOI: 10.24193/subbchem.2017.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different extraction techniques for the evaluation of polyphenols content in Summer savory extracts

Abstract: ABSTRACT. Efficiency of conventional solvent extraction (maceration and normal refluxing) and novel extraction techniques (ultrasound-assisted extraction-UAE and microwave-assisted extraction-MAE) were compared in order to obtain an enhanced content of total flavonoid, total phenolic compounds and rosmarinic acid from the Satureja hortensis L. (Summer savory) herb. Different mixtures of ethanol-water ratio were used for extraction of these compounds from dry plant material. High level of total flavonoid conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Derivatives of HCA are common for plants belonging to the family Lamiaceae. Rosmarinic acid, is often one of the major polyphenol constituents in aerial parts polar extracts of these plants, including plants of the genus Satureja [28][29][30][31][32] . Besides rosmarinic acid, Lamiaceae species produce higher HCA oligomers which contain up to 8 monomer units 33,27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Derivatives of HCA are common for plants belonging to the family Lamiaceae. Rosmarinic acid, is often one of the major polyphenol constituents in aerial parts polar extracts of these plants, including plants of the genus Satureja [28][29][30][31][32] . Besides rosmarinic acid, Lamiaceae species produce higher HCA oligomers which contain up to 8 monomer units 33,27 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority (14) of eighteen identi ed avonoids, were avones, i.e. aglycons luteolin (29), apigenin (32), and genkwanin (34), as well as glycosides of luteolin (5, 8, 10, 11, 13, and 16) and apigenin (6 and 14) and their methylated derivatives (17, 23, and 26) (Table 1). The MS data obtained in the analysis of extracts and available standards, indicated that the sugar moieties of glycosides were either monosaccharide (hexose or hexuronic acid) or disaccharide units (composed of two hexuronic acids or deoxyhexose and hexose).…”
Section: Qualitative Composition Of the Extractsmentioning
confidence: 99%
“…Derivatives of HCA are common for plants belonging to the family Lamiaceae. Rosmarinic acid is often one of the major polyphenol constituents in aerial parts of polar extracts of these plants, including plants of the genus Satureja [34][35][36][37][38] . Besides rosmarinic acid, Lamiaceae species produce higher HCA oligomers which contain up to 8 monomer units 33,39 .…”
Section: Discussionmentioning
confidence: 99%